Komunikasi Getok Tular dan Metode Dakwah Hizbut Tahrir Indonesia - Udin, Muhammad Diak; Muhid, Abdul (Jurnal Komunikasi Islam, 2018)
This study aims to explain how the use of word of mouth communication (getok tular) and the rationale behind the usage as a method of da’wah within Hizbut Tahrir Indonesia (HTI). This study used a qualitative approach with a case study design. The results of the study revealed that the word of mouth communication was applied for two activities, namely as a method of delivering da’wah messages and as a method of cadre with a chain system to official members who were stratified based on the study book or HTI curriculum. The reason why HTI used word of mouth communication as a method of da’wah was because of the effectiveness and efficiency factors as well as socio-cultural factors.